DYNAMICS OF ANISOTROPIC SHARMA-MITTAL HOLOGRAPHIC DARK ENERGY MODEL IN BRANS-DICKE THEORY - Vijaya Prasanthi A; Suryanarayana G; Aditya Y; Divya Prasanthi U Y (Proceedings on Engineering Sciences)
The Brans-Dicke scalar-tensor theory of gravity (Phys. Rev. 124, 925: 1961) is applied in this work to study the Sharma-Mittal holographic dark energy on a background of anisotropic and spatially homogenous Bianchi type-II spacetime. In this scenario, the Brans-Dicke scalar field ϕ is used as a function of the average scale factor a(t). To explore the universe's accelerated expansion, the physical behaviour of the model is addressed through a graphical representation. Furthermore, squared sound speed V22 is used to verify the stability of the models. The popular cosmic plane ωde - ω' de is built for our models. It's also important to note that all the findings are in line with current observational data.